Handbook of statistical analysis and data mining applications - Nisbet, Robert; Miner, Gary; Yale, Ken; Elder, John; Peterson, Andy (Academic Press, 2018)
A comprehensive professional reference book that guides business analysts, scientists, engineers and researchers, both academic and industrial, through all stages of data analysis, model building and implementation. The handbook helps users discern technical and business problems, understand the strengths and weaknesses of modern data mining algorithms and employ the right statistical methods for practical application. This book is an ideal reference for users who want to address massive and complex datasets with novel statistical approaches and be able to objectively evaluate analyses and solutions.